Brain Natriuretic Peptide for Predicting Contrast-Induced Acute Kidney Injury in Patients with Acute Coronary Syndrome Undergoing Coronary Angiography: A Systematic Review and Meta-Analysis. (19th September 2020) - Li, Xiaoming; Liu, Chao; Mao, Zhi; Qi, Shuang; Song, Renjie; Zhou, Feihu
Abstract : Objective . To assess the diagnostic value of B-type natriuretic peptide (BNP) or N-terminal pro-B-type natriuretic peptide (NT-proBNP) for contrast-induced acute kidney injury (CI-AKI) in patients with acute coronary syndrome (ACS) undergoing coronary angiography. Background . ACS remains a major cause of death worldwide. Patients with ACS undergoing coronary angiography are more likely to develop CI-AKI, which correlates highly with poor clinical outcomes. Early diagnosis of CI-AKI remains a challenge. Many recent studies have suggested that BNP or NT-proBNP may be a useful biomarker for the early diagnosis of CI-AKI. Methods . We searched databases (PubMed, EMBASE, and Cochrane Library) to identify eligible studies. Two authors independently screened the studies and extracted data. We used the Quality Assessment of Diagnostic Accuracy Studies 2 (QUADAS-2) criteria to assess the methodological quality of the included studies and STATA to perform all statistical analyses. Results . Nine studies including 2832 patients were identified. The pooled sensitivity of 0.73 (95% CI 0.65–0.79), specificity of 0.79 (95% CI 0.70–0.85), and area under the summary receiver operating characteristic curve of 0.81 (95% CI 0.77–0.84) suggested that BNP or NT-proBNP had a good diagnostic value for CI-AKI in patients with ACS undergoing coronary angiography. Conclusions . Our findings suggest that BNP or NT-proBNP may be an effective predictive marker for CI-AKI. However, additional high-quality studies are required to find the optimal cutoff value and the diagnostic value of BNP or NT-proBNP in combination with other biomarkers.